Description of the lungworm Otostrongylus circumlitus (Railliet, 1899) de Bruyn, 1933 (Metastrongyloidea: Crenosomatidae) found in the heart of harbour seals from Sweden (Journal of Nematode Morphology and Systematics, 2012)
The lungwormOtostrongylus circumlitus (Railliet, 1899) de Bruyn, 1933 is described from specimens collected from the heart of harbour seals (Phoca vitulina vitulina L., 1758) in Sweden. The material is compared with the original description of the species and specimens described from harbour seals in the English Channel, from ringed seals in the Sea of Okhotsk, and from Pacific harbour seals along the central California coast. The Swedish specimens are shorter than those of the original description and those from the Sea of Okhotsk. They are somewhat longer than those from the English Channel, but agree rather well with the Californian specimens in most morphometric characters. The size and shape of spicules and gubernaculum as well as the bursa and the organisation of bursal rays of the Swedish males agree with those described for the specimens from the English Channel, the Sea of Okhotsk, and California. New external morphological features, observed for the first time by SEM, revealed additional ventral bursal papillae which have not been reported before in this species.